KNOWLEDGE AND UNDERSTANDING ABOUT PREPARATION OF HOUSEHOLD ACCOUNTS OF THE VILLAGERS OF KOTARANA COMMUNITY KHONGMAI SUB-DISTRICT, YARANG DISTRICT, PATTANI PROVINCE, THAILAND - Suriaya Yusoh; Sri Dwi Estiningrum (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
This research aims to analyze the characteristics of income and cost behavior, procedures for accounting records in households and study the problems and obstacles in preparing household bookkeeping in Kotarana Village, Khlongmai sub-district, Yarang Regency Province,Pattani Thailand. The respondent analysis technique used was 74 people who had a fixed income. The analysis technique in this research is an interview using a questionnaire regarding knowledge of home bookkeeping stairs using statistical testing with frequency, mean and standard deviation. The research results show that the majority of respondents have a fixed income, an average of 4,001-10,000 bath with expenditure flat-average is 4,001-10,000 bath. Recording Household accounting is carried out to record income and expenses on a weekly basis. Factors that cause problems and obstacles in preparing household bookkeeping for the people of Kotarana Village. Most of the people of Kotarana Village experience problems in preparing themselves, namely having many responsibilities that are not continuous recording Household accounting and consistently lack of experience and complexity in household bookkeeping result in people wasting time and not being able to memorize income items that occur everyday. Knowledge The lack of understanding and resources for further studies to record household bookkeeping means that most farmer groups do not own continuous household bookkeeping records.